Cinnamaldehyde Suppressed EGF-Induced EMT Process and Inhibits Ovarian Cancer Progression Through PI3K/AKT Pathway - Wang, Yue; Li, Ying; Wang, Liang; Chen, Buze; Zhu, Miaolin; Ma, Chunyi; Mu, Chunyan; Tao, Aibin; Li, Shibao; Luo, Lan; Ma, Ping; Ji, Shuai; et al. (Frontiers in Pharmacology, 2022)
Ovarian cancer is one of the most common gynecological malignancies in women worldwide with a poor survival rate. Cinnamaldehyde (CA), a bioactive substance isolated from cinnamon bark, is a natural drug and has shown that CA inhibited the progression in other tumours. However, the role of CA in ovarian cancer and its mechanism are poorly understood. Wound healing assays, plate cloning, CCK-8 and transwell assays were used to determine cell proliferation and invasion. Western blot and flow cytometry were used to detect apoptosis levels. Western blot and immunofluorescence were used to detect changes in cellular EMT levels. Western blot was used to detect levels of the PI3K/AKT signaling pathway. In vivo, we established a subcutaneous transplantation tumor model in nude mice to verify the role of CA on the progression and metastasis of ovarian cancer. Our data showed that in vitro CA was able to inhibit the cell viability of ovarian cancer. The results of scratch assay and transwell assay also showed that CA inhibited the proliferation and invasion ability of A2780 and SKOV3 cells. In addition, CA promoted apoptosis by increasing the expression of Cleaved-PARP and Cleaved-caspase3 in ovarian cancer cells. Mechanistically, we found that CA inhibited the EGF-induced PI3K/AKT signaling pathway and reduced the phosphorylation levels of mTOR, PI3K, and AKT. EGF-induced EMT process was also abolished by CA. The EMT process induced by AKT-specific activator SC79 was also suppressed by CA. Furthermore, in vivo, CA significantly repressed the progression of ovarian cancer as well as liver metastasis. In all, our results suggest that CA inhibits ovarian cancer progression and metastasis in vivo and in vitro and inhibits EGF-induced EMT processes through the PI3K/AKT signaling pathway.